Espaços coletivos: espaços privados com áreas coletivas - Vianna, Norma Fonseca (2007)
Common spaces comprise areas of private usage which allows in its schedule spaces that intermarry to public usage. The aim of this work is to reflect upon the relations between public spaces and private spaces; to introduce the discussion over the role and the values of these spaces in present cities and how the Architect interferes in the city s schedule. Proposal of projects that contain common spaces are analysed, covering the following characteristics: urban requalification and the reestablishment of the fresh air sociability in a city needy of spaces; the integration between the State (public) and Empresarial strategies (private) with participative urban policies; the public possibility of the private project to establish itself in the urban level and to manifest itself on the city image trough the spaces of public sociability; the Symbolism and the dialog representation between the social fields, productive and ambient; common space of exchange, circulation and a net of connections between the blocks; the possibility of bigger retreats, shading, adequate flow and the reestablishment of the fresh air sociability in a city needy of spaces. Case studies, that covers three projects in São Paulo city, are accomplished, as follows: Cetenco Plaza, project of architects Rubens Carneiro Vianna and Ricardo Sievers; Itau Empresarial Center (CEIC), project of architects Jaime Cupertino and Francisco Javier; and Brascan Century Plaza, project of architects Jorge Konigsberger and Gianfranco Vannucchi.